Effects of timing of oral calcium administration on milk production in high-producing early-lactation Holstein cows - C.R. Seely; C.N. Wilbur; K.M. Fang; J.A.A. McArt (Journal of Dairy Science, 2024)
ABSTRACT: Supplementation of oral Ca via blanket administration of an oral Ca bolus at 0 and 24 h after calving has shown limited success in increasing production and minimizing adverse health events. Recent evidence that reductions in blood Ca at 4 d in milk (DIM) are more closely associated with negative outcomes than hypocalcemia at 0 to 24 h postpartum might explain this lack of Ca bolus efficacy. Therefore, our primary objective was to explore the effect of delayed oral Ca bolus supplementation on milk production, with secondary objectives of exploring the effects on disease incidence and postpartum blood Ca dynamics. We conducted a randomized controlled trial on multiparous Holstein cows (n = 998) from 4 herds in New York. At calving, cows were randomly assigned to 1 of 3 treatment groups: (1) control, no supplemental Ca at or around parturition (CON; n = 343); (2) conventional bolus, an oral Ca bolus containing 43 g of Ca at calving and 24 h later (BOL-C; n = 330); or (3) delayed bolus, an oral Ca bolus containing 43 g of Ca at 48 and 72 h after calving (BOL-D; n = 325). We created generalized linear mixed models to analyze differences in milk yield for the first 10 wk of lactation and serum total Ca (tCa) at 1 and 4 DIM between treatment groups; multivariable Poisson regression models were used to analyze adverse event outcomes (metritis, displaced abomasum, herd removal, or a combination of one or more of the 3) in the first 30 DIM. Milk yield increased by week and was not affected by treatment. However, a treatment by parity group interaction for milk yield showed that BOL-D cows in the third parity produced more milk than third-parity BOL-C or CON cows (BOL-D = 52.0 kg/d, 95% confidence interval [50.6, 53.4] kg/d, BOL-C = 47.9 [46.3, 49.5] kg/d, CON = 49.8 [48.2, 51.2] kg/d). The incidence of adverse health events was similar between treatments (BOL-D = 3.7%, BOL-C = 3.7%, CON = 3.6%). Serum tCa was lower at 1 than 4 DIM, and we detected no difference in tCa between treatment groups. Our findings suggest that delaying oral Ca bolus supplementation has limited influence on blood Ca concentrations but may be beneficial to cohorts of cows as a targeted prophylactic supplement to support milk production.